PENERAPAN METODE ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INGGRIS MATERI ANNOUNCEMENT PADA SISWA KELAS X MIPA 1 SMA NEGERI 1 GIRIMARTO SEMESTER 2 TAHUN PELAJARAN 2021/2022 - suwati wati (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2023)
The research is done to know the increasing of studying result of students class X MIPA 1 SMA Negeri 1 Girimarto, Wonogiri, Central Java, By Implementation Role Playing Method of English lesson Material of Announcement. This Research is Class Action research that done at least 2 cycles. Subject of research are 36 students of class X MIPA 1 SMA N 1 Girimarto. Technic of submitting data of students studying result by studying result test. Technic of data analysis is kuantitatif data analysis, It is the average of test value of student studying. The result of this research increase studying result of students class X MIPA 1 SMA Negeri 1 Girimarto at Semester 2 2021/2022 by implementation of Role playing method that proved by increasing the average value of the students studying result and the completeness of students learning. The increasing of students results at pre cycle showed the student average value is 56,26 or 13,89 % students had completed. Cycle 1 of studying Result of students have not reached minimum completed criteria, 41,67 %, with the class average value 66,67 % that still under KKM value >_ 70 and completeness prosentase KKM >_ 70 %. At cycle 2 the result of students studying had reached KKM ( Minimum Completeness Criteria ) 86,11 % with the class average value 83,61 and already beyond KKM value. From this research data can be concluded that the implementation of Role Playing Method had success increased result studying of English the material of Announcement so worthy to applied at SMA Negeri 1 GirimartoWonogiri, Central Java.